2008
DOI: 10.1016/j.pbb.2008.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Nonselective suppression of operant ethanol and sucrose self-administration by the mGluR7 positive allosteric modulator AMN082

Abstract: Emerging evidence indicates that specific metabotropic glutamate receptors (mGluRs) modulate ethanol self-administration. In general, inhibition of glutamate transmission through blockade of postsynaptic mGluRs, or activation of presynaptic mGluRs, inhibits ethanol self-administration. The goal of this preclinical study was to further characterize mGluR regulation of ethanol selfadministration by examining effects of AMN082, an allosteric positive modulator of presynaptic mGluR7 activity. Separate groups of C5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
49
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 49 publications
6
49
1
Order By: Relevance
“…In fact, when C57BL/6J male mice were trained to self-administer ethanol or sucrose, it was reported that AMN082 produced a significant reduction in ethanol and sucrose reinforced responding and inhibited locomotor activity (Salling et al, 2008). Vadasz et al (2007) when using near-isogenic advanced animal models with reduced genetic background interactions, were able to identify mGluR7 as a cis-regulated gene for ethanol consumption.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, when C57BL/6J male mice were trained to self-administer ethanol or sucrose, it was reported that AMN082 produced a significant reduction in ethanol and sucrose reinforced responding and inhibited locomotor activity (Salling et al, 2008). Vadasz et al (2007) when using near-isogenic advanced animal models with reduced genetic background interactions, were able to identify mGluR7 as a cis-regulated gene for ethanol consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Presumably this excess glutamate stimulates mGluRs in these brain regions. It is likely (although not yet demonstrated) that ethanol-induced glutamate activity participates in adaptive processes, such as those involved in sensitization, tolerance, withdrawal, and relapse (Bahi, 2011;Bahi et al, 2012;Salling et al, 2008). The receptor basis for these effects is poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…However, in contrast with mGluR2/3 stimulation, mGluR7 activation augments glutamate and GABA release (Li et al, 2013). Systemic administration of AMN082 (N,N9-dibenzhydrylethane-1,2-diamine dihydrochloride), a selective mGluR7 agonist, inhibits cocaine intake and cocaine-and heroin-primed reinstatement (Li et al, 2010), as well as ethanol intake and ethanol-primed CPP (Salling et al, 2008;Bahi et al, 2012). Interestingly, microinjection of the mGluR7 agonist AMN082 in Fig.…”
Section: E Group III Metabotropic Glutamate Receptors (Metabotropic mentioning
confidence: 98%
“…AMN082 has been used extensively to interrogate the role of mGluR7 activation in vivo and has been reported to produce broadspectrum activity across a number of preclinical models including anxiety and depression (Mitsukawa et al, 2005;Palucha et al, 2007;Dolan et al, 2009;Li et al, 2009;Greco et al, 2010), results that would not have been predicted based on the phenotype of the mGluR7 knockout mice. However, at the doses required to observe efficacy in a number of these preclinical models, nonspecific behaviors are also often reported such as tremors and reduced locomotor activity (Palucha et al, 2007), thereby suggesting possible off-target effects of AMN082 (see discussion in Salling et al, 2008). These conflicting reports, coupled to an initial hypothesis that antagonists of mGluR7 would be predicted to have anxiolytic-and antidepressant-like activity, prompted us to extend the in vitro and in vivo characterization of AMN082 to evaluate its pharmacokinetic and metabolite profiles to help elucidate the mechanism by which this compound might be producing efficacy in preclinical models predictive of antidepressant-like activity.…”
Section: Introductionmentioning
confidence: 99%